2017
DOI: 10.21175/radj.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Foramen Position in Relation to the Radiographic Apex of the Mandibular Second Premolar

Abstract: Abstract. The identification of the mental foramen is important for both diagnostic and clinical procedures. The knowledge about its accurate location is significant in reducing complications that may occur during surgical and endodontic treatments involving the mental area. The purpose of this study was to determine the position of mental foramen in relation to the radiographic apex of the mandibular second premolar on panoramic radiographs. Two hundred digital panoramic radiographs were analyzed in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Our study findings are similar to the findings of the study done by various authors in different population reported similar findings. [14][15][16]21,26,28 In contrast to finding of our study, statistically significant difference (p < 0.05) in symmetry of location of MF was found between the genders by Al-Shayyab et al and Suragimath et al 10,18 Intra-observer reliability in localization of MF…”
Section: Comparison Of Position Of Mf Between Genderscontrasting
confidence: 78%
See 2 more Smart Citations
“…Our study findings are similar to the findings of the study done by various authors in different population reported similar findings. [14][15][16]21,26,28 In contrast to finding of our study, statistically significant difference (p < 0.05) in symmetry of location of MF was found between the genders by Al-Shayyab et al and Suragimath et al 10,18 Intra-observer reliability in localization of MF…”
Section: Comparison Of Position Of Mf Between Genderscontrasting
confidence: 78%
“…However, according to Popovic et al there was no statistically significant difference in symmetry of location of MF. 28 As there is no single study showing 100% of symmetry in position of MF on both sides, it clearly indicates that MF is not always symmetrical even in same individuals. 10…”
Section: Symmetry In Localization Of Mf Between Right and Left Side O...mentioning
confidence: 99%
See 1 more Smart Citation